PENCIPTAAN TOMBAK DHAPUR IKAN KOI - Listiani, Yuni; Yuwono, Basuki Teguh (Institut Seni Indonesia Surakarta, 2022)
Koi fish (Cyprinus carpio) is a type of ornamental fish that easily adapts to its new environment, this fish is classified as carp (carp). Koi have senses in the form of a pair of eyes (sight), nose (smell), and antennae (taste). And has a swim bladder that helps in swimming such as floating, swooping, or looking up. The creation method used in the process of creating this koi fish spear uses the theory of S.P. Gustami, namely: the first stage of exploration which includes exploration activities to explore sources of ideas through observation, literature study, interviews, and documentation by collecting data in the form of references to writings, pictures, journals, final project reports, photographs of works, photos of objects related to theme. The two design stages include ideas in the form of alternative sketches, selected designs, and working drawings. The three stages of embodiment include the final process starting from the forging, grinding, turning, nyangkling, tinatah, ngamal and warangi processes. Koi fish are a source of inspiration for writers because of the attractive, beautiful, symbolic aspects, meanings and benefits that can be visualized into spear work. Spear is a traditional weapon that is found in all civilizations of the world, during the stone age. Derived from a pointed stone that is given a long stalk, the tool is used for hunting, fishing, and fighting. Over time, spears were used for traditional ceremonies, and were used as heirlooms for generations.